2019
DOI: 10.7717/peerj.7174
|View full text |Cite
|
Sign up to set email alerts
|

Freshwater reservoir offsets on radiocarbon-dated dog bone from the headwaters of the St. Lawrence River, USA

Abstract: Isotopic analysis of dog (Canis lupus familiaris) bone recovered from archaeological sites as proxies for human bone is becoming common in North America. Chronological placement of the dogs is often determined through radiocarbon dating of dog bone. The Great Lakes, their tributaries, and nearby lakes and streams were important fisheries for Native Americans prior to and after sustained European presence in the region. Carbon entering the food web in freshwater systems is often not in full isotopic equilibrium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…familiaris ) bone, which appear to have offsets relative to ages on maize ( Zea mays ssp. mays ) and/or white-tailed deer ( Odocoileus virginianus ) from the same sites (Hart, Feranec et al 2019). We also eliminated an erroneous date on white-tailed deer bone from the St. Lawrence site (UCIAMS-204716), bulk sample dates as discussed above, and a modern determination from Whitford (UGAMS-30329).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…familiaris ) bone, which appear to have offsets relative to ages on maize ( Zea mays ssp. mays ) and/or white-tailed deer ( Odocoileus virginianus ) from the same sites (Hart, Feranec et al 2019). We also eliminated an erroneous date on white-tailed deer bone from the St. Lawrence site (UCIAMS-204716), bulk sample dates as discussed above, and a modern determination from Whitford (UGAMS-30329).…”
Section: Methodsmentioning
confidence: 99%
“…Over the last 30 years, the Iroquoian occupations of Northern New York have received a renewed research focus. Reanalyses of older data (Engelbrecht 1995, 2004; Engelbrecht et al 1990), in conjunction with the publication of new excavations and analyses (Abel 2001, 2015, 2016; Baron et al 2016; Dermarkar et al 2016; Engelbrecht and Jamieson 2016a, 2016b; Hart et al 2017; Hart, Winchell-Sweeney, and Birch 2019; Jones et al 2018; Vavrasek 2010; Wonderley 2005), have greatly increased our understanding of this once-enigmatic region and period (Abel 2019a). As a result of this research, it is apparent that the region and its inhabitants played a far more integral role in the broader social, economic, and political fabric of greater Iroquoia than had been previously acknowledged.…”
mentioning
confidence: 99%
“…The location of Ewing site (Shelburne Pond) contains dolomite that could cause a reservoir effect as 14 C depleted carbon dissolves from bedrock into the water and is taken up into non-emergent aquatic vegetation (Lini et al, 2007). While Hart et al (2019) found a freshwater offset of 132 ± 8 14 Cyr for dogs consuming freshwater resources on the St. Lawrence River, Plint et al (2019) did not include such an offset for paleontological beaver remains, and beavers are known to rely on terrestrial vegetation (Supplementary material); therefore, we did not apply a freshwater reservoir correction. Our muskrat and beaver radiocarbon dates are in line with expectations from contextual charcoal-based dates from the site that would be unaffected by this reservoir effect (Supplementary Figure 1).…”
Section: New Beaver and Muskrat Radiocarbon Datesmentioning
confidence: 99%
“…It is important to note that, unlike the correction used for anadromous fish, the equation used for potamodromous fish does not account for temporal offsets related to the complexities of freshwater aquatic carbon cycling. An increasing number of 14 C studies highlight the wide range of variation that can occur in the age and reservoir period for DIC used by primary producers at the base of freshwater environments, which can extend to hundreds and even thousands of years [e.g., [103][104][105][106][107][108][109][110]. This offset means that there may be considerable temporal lag between the impact of the Suess effect on the isotopic composition of atmospheric and freshwater DIC pools.…”
Section: Carbon Isotope Correctionsmentioning
confidence: 99%